Committees planning meeting. - Indian Students' Association:::Creator::::::::::::
Poster promoting a meeting of Indian Students' Association to assemble a committee to organize forums regarding current political and social situations in India and a committee to arrange cultural programs. All interested students were invited. The meeting was held in Tan Oak Room at UC Berkeley.